0150 Exploring Associations Between Sleep Spindle Characteristics and Circadian Preference in Adults. (12th April 2019) - Rodheim, Katrina; Fitzroy, Ahren; Jones, Bethany; Holmes, Jen; Lokhandwala, Sanna; Spencer, Rebecca
Abstract: Introduction: Decreased spindle amplitude and intensity has been found to be related with circadian preference for morningness in adolescents. However, it is unknown whether this is the case in adults. Thus, this analysis aims to look at the relationship between adult Horne-Ostberg Morningness-Eveningness Questionnaire (MEQ) scores and polysomnography data to determine whether the same is true in adult populations. Methods: Participants (N=15, M=41.07 years) completed the MEQ to determine their personal circadian preference. Polysomnography was recorded in participants' homes using the Aura PSG ambulatory system (Grass Technologies) during overnight sleep. Sleep architecture, was analyzed using a combination of EEGlab and Matlab. Results: Sigma density means in NREM2 did not significantly correlate with MEQ scores in adults (p = 0.31). However, sigma density means in NREM3 were negatively associated with circadian preference scores (R = -0.592, p = 0.055). Conclusion: These results suggest a trending negative association between spindle density in NREM3 and MEQ scores. This result is of interest as spindle activity is more typically seen in NREM2. These results suggest a similar association as seen between spindles and circadian preference in adolescents in NREM2 sleep. Future analysis will include more participants to further explore the possible association between MEQ and spindle density. Spindle characteristics such as amplitude and intensity will also be included. Support (If Any): This work was funded by NIH R01 AG040133 (PI: Spencer)